A review of group B streptococcus (Gbs) vaginal colonization and ascending intrauterine infection: interaction between host immune responses and gbs virulence factors - Wahid, Hanan Hamimi; Mustapha Rounal, Puteri Farah Diba; Bahez, Ayesha; Mustafa, Imad Al-Deen; Kamarudin, Norhidayah; Selvakumaran, Arvind R.; Ahmad Mustafa, Ahmad Mujahid; Ismail, Hamizah (Zibeline International Publishing, 2022)
Vaginal colonization with Group B streptococcus (GBS) or Streptococcus agalactiae can potentially cause ascending intrauterine infection among pregnant women, and hence it is known as one of the risk factors for preterm delivery. Ascending intrauterine infection may also cause the transmission of GBS to the fetus in utero and the newborn during delivery, leading to the development of early onset of neonatal infection. GBS are βhemolytic, gram-positive bacteria that are opportunistic commensal of the gastrointestinal and urogenital tract of approximately 18% of pregnant women globally. Intrapartum antibiotic prophylaxis (IAP) only reduces the rate of early onset neonatal infection, but not the late onset neonatal infection. Thus, the development of GBS vaccine is thought to be important to decrease the rate of preterm delivery and neonatal infections particularly in low-and-middle income countries where IAP program is not feasible. Vaccination can also be cost-effective for the healthcare system when executed together with IAP program. The aim of the current review is to summarize the mechanisms on how the GBS virulence factors interact with host immune components in the gestational tissues, leading to cervicovaginal colonization and ascending intrauterine infection. The elucidation of these mechanisms is essential for expediting the development of vaccines and novel therapeutic measures targeting these GBS virulence factors that will hamper the vaginal colonization, ascending intrauterine infection and conceptus tissue invasion by GBS. These strategies are crucial to potentially reduce the rate of preterm delivery and subsequent serious complications in the newborn.